2015
DOI: 10.3389/fnins.2015.00396
|View full text |Cite
|
Sign up to set email alerts
|

Assessing intracortical myelin in the living human brain using myelinated cortical thickness

Abstract: Alterations in the myelination of the cerebral cortex may underlie abnormal cortical function in a variety of brain diseases. Here, we describe a technique for investigating changes in intracortical myelin in clinical populations on the basis of cortical thickness measurements with magnetic resonance imaging (MRI) at 3 Tesla. For this, we separately compute the thickness of the shallower, lightly myelinated portion of the cortex and its deeper, heavily myelinated portion (referred to herein as unmyelinated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 60 publications
6
61
0
Order By: Relevance
“…Figure 5 maps these values across the cortex both from vertex-wise fits and from fits of signal averaged over the ROIs. The signal maximum plots (k) resemble previously reported myelin maps derived from MRI [Bock et al, 2013;Dinse et al, 2015;Glasser and Van Essen, 2011;Lutti et al, 2014;Rowley et al, 2015;Waehnert et al, 2016], with high signal intensity in primary cortical areas, and lower intensity in association regions. The age where the signal reaches a maximum in the fit shows that the visual regions, cingulate, and left ventromedial prefrontal cortex peak first, and the premotor and primary motor cortices peak last.…”
Section: Estimating Maximum Value From Fitssupporting
confidence: 79%
“…Figure 5 maps these values across the cortex both from vertex-wise fits and from fits of signal averaged over the ROIs. The signal maximum plots (k) resemble previously reported myelin maps derived from MRI [Bock et al, 2013;Dinse et al, 2015;Glasser and Van Essen, 2011;Lutti et al, 2014;Rowley et al, 2015;Waehnert et al, 2016], with high signal intensity in primary cortical areas, and lower intensity in association regions. The age where the signal reaches a maximum in the fit shows that the visual regions, cingulate, and left ventromedial prefrontal cortex peak first, and the premotor and primary motor cortices peak last.…”
Section: Estimating Maximum Value From Fitssupporting
confidence: 79%
“…For example, MRI measures that are sensitive to intracortical myelin have revealed a pattern of high myelin content in primary sensorimotor regions, which systematically decreases toward transmodal areas in parietal, temporal, and particularly prefrontal cortex [3,[25][26][27][28] (Figure 1A). A similar spatial distribution has been described for MRI-based measures of cortical thickness [12] and myelinated thickness [29]. Cortical thickness coarsely tracks changes in cytoarchitecture [30] and myelin content [25], and can be viewed as a pragmatic surrogate for cortical microstructure [12].…”
Section: Glossarymentioning
confidence: 77%
“…Recent studies in that field have shown a stronger intracortical myelination particularly within primary sensory areas such as PAC (Glasser et al, 2016;Glasser & van Essen, 2011;Shafee et al, 2015;Van Essen, Glasser, Dierker, Harwell, & Coalson, 2012;Wasserthal et al, 2014), and furthermore leftlateralized myelination in HG suggesting a link to language function (Sigalovsky et al, 2006). In fact, the highest proportion of heavily myelinated deeper layers of the cortex has been found in the precentral and postcentral gyrus as well as in the core region of HG (Rowley et al, 2015). Thus, area-specific differences in intracortical myelination should be considered when using novel automated methods for CTH estimation based on T1 images, as the exact GM-WM border of the higher myelinated primary cortex may be difficult to determine within the deeper cortical layers (Glasser & van Essen, 2011).…”
Section: Localization and Lateralization Of Pacmentioning
confidence: 99%